Impacto do crédito rural e seguro rural na produção agrícola no estado de São Paulo - Leite, Francisca Nathalia de Sousa (2020)
Rural credit and rural insurance have an important role for the agricultural sector, once they are the main public policies to incentive agricultural production. Rural credit reduces the farmers's budget constraint, finances production costs and the use of new technologies. Rural insurance protects farmer’s income from production losses. Public resources subsidize the rural credit through the application of lower interest rates to the agricultural sector and rural insurance through the Rural Insurance Premium Subvention Program - PSR, “Proagro” and “Proagro Mais”. Given the importance the agricultural sector has on the Brazilian economy and the participation of public resources to sustain these policies, this research aimed to evaluate their efficiency for sugarcane, grains (soybeans, corn and wheat) and grape crops in São Paulo state. It is analyzed the data from “Agricultural Production Systematic Survey” (LUPA) in its more disaggregated level, the Agricultural Production Unity (UPA), for the years 2007/2008 and 2017/2018. It is analyzed the impact of rural credit and rural insurance policies in production, productivity and cultivated area. The analysis uses the methodology Propensity Score Matching (PSM) which allows to compare the groups that have used these programs and those groups that have not. We conclude that the rural credit and rural insurance policies impact the analyzed variables for grain and grape crops. However, for sugarcane crop the rural credit crop did not impact the production, productivity or cultivated area and the rural insurance impacted these variables only in the year of 2017/18.